Semantic image segmentation and cosegmentation - Zhu, Hongyuan (2015)
This thesis considers the challenging problem of automatically segmenting an image or a photo stream into a few number of regions that correspond to semantic objects or high-level structures, which can be highly beneficial for various computer vision tasks given existing huge amount of images over the internet.